Comparative Study of Development and Performance Evaluation Sharia Microfinance Institutions in Indonesia - Vanni, Kartika Marella; Wijayanti, Riska (AL-ARBAH: Journal of Islamic Finance and Banking, 2020)
Purpose - This paper aims to determine the role of Islamic Microfinance Institutions (LKMS) in Indonesia and to make comparisons between theory and practice in the field.Method - The method used is a descriptive qualitative approach in which data collection is taken from a study of various literature and then compared with previous studies related to the discussion.Result - Sharia Microfinance Institutions theoretically play a role to help improve the national economy and alleviate community poverty by embracing the lower class and all remote areas. Meanwhile, empirically, Islamic Microfinance Institutions have tried to carry out their operational activities in accordance with the provisions and principles of Sharia, but there are still internal and external constraints.Implication - This study examines Islamic Microfinance Institutions in Indonesia.Originality - There are differences between theory and practice in Islamic Microfinance Institutions in Indonesia.